Criminal Law Politics Renewal of The National KUHP Against the Criminal Actions of Lesbian, Gay, Bisexual, Transgender (LGBT) - Sugiarto, Agus (Riviera Publishing, 2022)
Introduction: LGBT issues have returned to the surface following the World Pila event in Qatar, the earthquake in Cianjur and the ratification of the Draft Indonesian National Criminal Code. This study aims to analyze: Regulation of Lesbian, Gay, Bisexual, Transgender (LGBT) Obscene Acts in positive national Law, Legal Politics of Indonesian Criminal Law Renewal of Lesbian, Gay, Bisexual, Transgender (LGBT) Obscene Acts of Crime in law positives to come. Method: This study uses a normative juridical method. Result: 1) The crime of committing an act of violating decency with the same sex or often referred to as LGBT, the regulations in Article 292 of the Criminal Code are Positive Dutch Colonial heritage when studied and analyzed, these regulations are multi-interpretable, giving rise to various pros and cons in society, which interpret that fellow adults or fellow children can do LGBT if it is done voluntarily. 2) Legal Politics Renewal of Indonesian Criminal Law The Criminal Act of Lesbian, Gay, Bisexual, and Transgender (LGBT) Obscene acts in positive law will come according to the concept of Article 420 of the Criminal Code Bill-Sep-2019 by ignoring the three main pillars of the Nation, namely the Proclamation, Pancasila and the 1945 Constitution of the Republic of Indonesia, articles which are multi-interpreted and winged, so that these articles are not following the Nation's values which are based on the Basic values of Belief in the One and Only God. Conclusion: Legal Politics Renewal of Indonesian Criminal Law the Criminal Acts of Lesbian, Gay, Bisexual, and Transgender (LGBT) Obscene acts in positive law will come according to the concept of Article 420 of the Criminal Code Bill-Sep-2019 by ignoring the three main pillars of the Nation, namely the Proclamation, Pancasila and the 1945 Constitution of the Republic of Indonesia.